Fungal Contamination of Consumed Tea in East Azarbaidjan Province - A Kazemi; J Mohtadi Nia; F Rezaeian; F Zamene Milani; M Vahed Jabbari; SJ Ghaem Maghami; R Mahdavi; AR Ostad Rahimi (Institue of Medicinal Plants, ACECR, 2009)
Background & Objective: Information on the fungal contamination of consumer tea is limited and this kind of contamination is important for food and therefore a survey was undertaken to determine the fungal contamination of consumer tea in East Azarbaidjan province. Methods: A total of 100 samples were obtained using standard 20 cm collection sond from whole sales and stores in different part of East Azarbaidjan province and examined according standards methods, Samples were cultured in YCFA medium and incubated at 25ºC for maximum 3 weeks and a screening survey for positive samples was carried out. Results: 73 (73%) out of total 100 samples had fungal contamination more than 104 colony forming units/gram (cfu/g), Aspergillus niger, Penicillium Sp, Fusarium Sp, Asergillus fumigatus, Alternaria Sp, Cladesporium Sp, Mucor Sp, Gliocladium Sp and Trichotecium Sp were the most frequently detected microorganisms throughout the survey respectively. Conclusion: The presence of moulds such as Aspergillus Sp, Penicillium Sp, Fusarium Sp, Alternaria Sp, Cladesporium Sp, Mucor Sp, Gliocladium Sp and Trichotecium Sp in consumer tea can lead to the presence of harmful mycotoxins produced by these moulds and then could result in serious toxicity and illness in humans, As the fungal contamination has a strong influence on the ultimate quality of tea, tea end products and food safety, more attention to the quality and safety of tea are necessary.